2016
DOI: 10.1016/j.appet.2016.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Associations of reward sensitivity with food consumption, activity pattern, and BMI in children

Abstract: 26In the current study, the associations of reward sensitivity with weight related behaviors and body 27 mass index were investigated in a general population sample of 443 Flemish children (50.3% boys) 28 aged 5.5-12 years. Cross-sectional data on palatable food consumption frequency, screen time,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 50 publications
3
44
2
7
Order By: Relevance
“…Thereby, RS was measured with a questionnaire that is easily and practically applicable for prevention purposes. The suggested increased risk for high RS girls is assumed to be explained by a higher vulnerability to palatable food cues in the environment (Paquet et al, 2010), followed by a higher motivation to obtain the food and resulting in higher consumption of these energy-dense foods (De Cock et al, 2016;De Decker et al, 2016). However, this was not tested in the current study.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Thereby, RS was measured with a questionnaire that is easily and practically applicable for prevention purposes. The suggested increased risk for high RS girls is assumed to be explained by a higher vulnerability to palatable food cues in the environment (Paquet et al, 2010), followed by a higher motivation to obtain the food and resulting in higher consumption of these energy-dense foods (De Cock et al, 2016;De Decker et al, 2016). However, this was not tested in the current study.…”
Section: Discussioncontrasting
confidence: 48%
“…Cross-sectional studies on this association in children reported a positive association with BMI but did not consider sex differences (De Decker et al, 2016;Verbeken et al, 2012). In young adults, a longitudinal study did not find a significant relation between scores on a different general RS-questionnaire and FMI increase, but no sex differences were tested (Finlayson, Cecil, Higgs, Hill, & Hetherington, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children and adolescents, RS has been positively associated with palatable food consumption [17,18]. Moreover, food cue responsiveness has been identified as a mediator of the relation between RS and palatable food consumption in adolescents [16].…”
Section: Introductionmentioning
confidence: 98%
“…1). In this context, fast food is seen as a relevant category of palatable, energydense, nutrient-poor food; its consumption frequency has already been related to RS in a previous study [18]. In addition, it is assumed that the moderation effect of the parameter 'unhealthy home environment' is exerted on the relation between food cue responsiveness and the fast-food consumption frequency based on theory (i.e.…”
Section: Introductionmentioning
confidence: 99%